Cross-cultural consumer perceptions of service quality in restaurants. Issue 6 (14th November 2016) - Djekic, Ilija; Kane, Kevin; Tomic, Nikola; Kalogianni, Eleni; Rocha, Ada; Zamioudi, Lamprini; Pacheco, Rita
Abstract : Purpose: This paper aims to present results from a research that analyzed consumer perceptions of service quality in restaurants in four European cities – Belgrade (Serbia), Manchester (UK), Thessaloniki (Greece) and Porto (Portugal). Design/methodology/approach: A total of 802 respondents have been interviewed using a structured questionnaire. The service quality statements covered food quality, building exterior, restaurant interior and layout, seating comfort, restrooms and servicing. Findings: Within all analyzed categories (city, gender and age), servicing of food and taste of food were the most influential factors. However, this study confirmed that there are different patterns in analyzed cities. For each factor analyzed, in at least two cities, results for the items were significantly different. Consumers from different cities showed different perceptions regarding service quality in restaurants. Gender of consumers plays a significant role in the perception of interior, restroom and servicing factors in restaurants. Age of respondents was the category with no significant difference with respect to food quality, layout, restrooms and servicing. Research limitations/implications: Given the great cultural and other differences within the four cities/countries, more research is necessary to determine if similar results would be derived from different samples across various other continental and Mediterranean European cities. Originality/value: In addition to increasing the theoretical understanding of the cultural aspects of the service quality, this paper can be of managerial relevance.